New forms of spirituality and the threat of sects in the context of religious security - Tomasz Czura; Ewelina, Anna Mączka (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2020)
The presented article is an attempt to show the relationship between the emerging new forms of spirituality and the threat of sects. The authors analyze the contemporary cultural context in terms of widely understood spirituality. They then come to the conclusion that subjectivization of religion leads to destabilization of the religious life of a given community and gives rise to possibilities of abuse in the religious space. At the same time, the authors are aware of the urgent need to free religion from ossification, passivity, the feeling of siege, excessive institutionalisation. However, they want to draw attention to the dangers resulting from the simplification that is increasingly being heard, which can be formulated as follows: Let us move religion into the private sphere, and the problems of religious conflicts and abuses connected with spiritual life will end. The authors draw attention to the fact that the problem is much more complex and requires coordinated action on religious security.